Optimal Cutoffs for the Diagnosis of Sarcopenia in Older Chinese Adults - Ge, Sheng; Du, Qin; Feng, Xiaohui; Liu, Yan; Wang, Hui; Hai, Shan; Shi, Xiaodong; Sun, Wenguang; Ma, Aiqin; Lv, Tingting; Liu, Haili; Pinupa, Venkata Saibaba; et al. (Frontiers in Nutrition, 2022)
Background The optimal criteria for sarcopenia in the older Chinese population have not been defined. Consequently, this study aims to determine the optimal cutoffs of grip strength, appendicular skeletal muscle index (ASMI) using bioelectrical impedance analysis (BIA), and gait speed, comprising the best definition of sarcopenia for older Chinese populations. Methods A total of 2,821 (1,398 men and 1,423 women) community-dwelling older people (≥60 years) and 409 (205 men and 204 women) young healthy adults (25–34 years) were recruited from three big cities in China. Besides gait speed and grip strength, we examined ASMI by BIA and dual-energy X-ray absorptiometry (DXA), comprising the three components of sarcopenia. DXA classification for low ASMI, 20th percentile among older adults in the study sample, was found to be best compared with the other existing classification, 1 SD and 2 SD below the mean for the young population, and was used as the gold standard to determine the optimal cutoffs of BIA using receiver operating characteristic curves (ROC). The cutoffs of handgrip strength and gait speed were determined following the same rule. Results Using gender-specific 20th percentiles of DXA (6.53 kg/m2 for men and 5.40 kg/m2 for women), the cutoffs 7.05 kg/m2 for men and 5.85 kg/m2 for women were determined as optimal cutoffs of BIA by achieving the largest sensitivity (0.81, 95% CI: 0.63–0.93 for men and 0.90, 95% CI: 0.73–0.98 for women) and specificity greater than 0.80 (0.80, 95% CI: 0.72–0.87 for men and 0.81, 95% CI: 0.72–0.87 for women) in the ROC analysis. The 28.5 kg and 1.05 m/s for men and 18.6 kg and 1.01 m/s for women were determined as the cutoffs for handgrip strength and gait speed, respectively. Based on the derived cutoffs, 14.2% of men and 15.7% of women in the older Chinese study population were classified as sarcopenia. Conclusion Notably, 7.05 kg/m2, 28.5 kg, and 1.05 m/s for men and 5.85 kg/m2, 18.6 kg, and 1.01 m/s for women were selected as the optimal cutoffs for low ASMI by BIA, handgrip strength, and gait speed, respectively. These optimal cutoffs will enhance practicability for screening sarcopenia in primary care and clinical settings.